ANALISIS RISIKO KESEHATAN LINGKUNGAN (ARKL) PAPARAN AMONIA (NH3) DI TEMPAT PENGOLAHAN SAMPAH REDUCE REUSE RECYCLE (TPS3R) SULUR BERKAH - Yolanda Margarettha Silaban (Jurnal Penelitian Kesmasy, 2026)
Background: Waste management at the Sulur Berkah 3R Waste Treatment Site (TPS3R) has the potential to release ammonia gas (NH₃) from organic waste decomposition, which may pose health risks to the community, particularly respiratory disorders. Objective: To analyze the Environmental Health Risk Assessment (ARKL) of ammonia (NH₃) exposure at the Sulur Berkah TPS3R. Methods: This was a descriptive quantitative study using the ARKL approach. The sample consisted of 55 respondents (workers and residents within a 60-meter radius) and 4 ambient air sampling points. NH₃ concentrations were measured using an impinger and spectrophotometer. Data analysis included hazard identification, dose-response assessment (RfC), exposure assessment (intake), and risk characterization (RQ). Results: The highest NH₃ concentration was found in the composting area (0.2234 ppm or 0.1556 mg/m³) and the lowest in residential areas (0.0299 ppm or 0.0208 mg/m³), with an average of 0.1148 ppm (0.0799 mg/m³) — all below the ambient air quality standard (2 ppm). The RfC value used was 0.5 mg/m³ (0.18 mg/kg/day). The highest real-time intake was 0.00518 mg/kg/day, and the highest lifetime intake was 0.02528 mg/kg/day. All real-time and lifetime (30-year projection) RQ values were < 1. Conclusion: NH₃ exposure at the Sulur Berkah TPS3R remains within safe limits and poses no risk (RQ < 1) to workers and surrounding residents, both currently and over a 30-year projection. Preventive risk management is still recommended to maintain these safe conditions.